2018
DOI: 10.3390/w10060780
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, Distribution, and Ecological Risk Assessment of Heavy Metals in Daya Bay, China

Abstract: Surface sediment samples were collected from 19 sites throughout Daya Bay, China to study the concentrations, spatial distributions, potential ecological risk, and possible sources of heavy, including metals copper (Cu), zinc (Zn), arsenic (As), cadmium (Cd), nickel (Ni), lead (Pb), mercury (Hg), and chromium (Cr). The mean concentrations of the eight heavy metals were 24, 109, 6.5, 0.09, 35.3, 26.8, 0.07, and 109 µg g −1 , respectively. The concentrations of most heavy metals were within range of those record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
1
20
1
Order By: Relevance
“…Zhao et al did not find high levels of Cd, Cr, Cu, Hg, or Zn in sediments from Daya Bay [12]. Tang et al reported that Cu, Zn, As, Ni, and Cr were below the acceptable limits, while Hg, Pb, and Cd exhibited moderate to high levels [13]. Liu et al reported the main contaminants were Cd and As, with their ecological risks "high" and "moderate" levels in sediments from Daya Bay [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Zhao et al did not find high levels of Cd, Cr, Cu, Hg, or Zn in sediments from Daya Bay [12]. Tang et al reported that Cu, Zn, As, Ni, and Cr were below the acceptable limits, while Hg, Pb, and Cd exhibited moderate to high levels [13]. Liu et al reported the main contaminants were Cd and As, with their ecological risks "high" and "moderate" levels in sediments from Daya Bay [14].…”
Section: Introductionmentioning
confidence: 98%
“…Chen et al and Qu et al analyzed trends and drivers of deteriorating water quality in Daya Bay [9,10]. Yang et al reported that HMs in surface sediments exhibited a zonal distribution, with a gradual decrease from nearshore to offshore [11]. Zhao et al did not find high levels of Cd, Cr, Cu, Hg, or Zn in sediments from Daya Bay [12].…”
Section: Introductionmentioning
confidence: 99%
“…With the diffusion of CO2 into the atmosphere, only heavier 13 C and 18 O remain [10]. Although coastal organic matter is complex due to its origin of marine organic matter and terrestrial plant detritus [11], the ratio of total organic carbon to total nitrogen (TOC to TN) and their stable isotope components (δ 13 CTOC and δ 15 NTN) under different sources can distinguish the sources of organic matter, which is helpful for reconstructing the evolution of the environment and the process of human activities [12][13][14][15][16][17]. Therefore, TIC, organic carbon and nitrogen, and their stable isotopic components are not only the main components of biogeochemistry in coastal sediments but also the main response indicators of environmental evolution [18].…”
Section: Introductionmentioning
confidence: 99%
“…I geo is calculated by computing the base 2 logarithm of the measured total concentration of the metal over its background concentration using the following equation:Where C n represents the measured concentrations of heavy metals and B n represents the geo-chemical background concentrations of the metals. Factor 1.5 was used as background value of lithological variability 12,13 .…”
Section: Methodsmentioning
confidence: 99%